Human Resource Quality and Organizational Culture in Employee Performance Assessment: Kualitas Sumber Daya Manusia dan Budaya Organisasi dalam Penilaian Kinerja Karyawan - Denayou Nabilla Rajabie; Desy Mardianti (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Employee performance remains a central concern in Islamic banking institutions operating in increasingly competitive service environments. Specific background: At PT Bank Riau Kepri Syariah Batam Branch, variations in employee competencies and internal organizational practices have raised questions regarding performance assessment outcomes. Knowledge gap: Existing studies tend to address human resources and organizational culture in general terms, with limited attention to concrete internal conditions such as educational mismatch, uneven technical skills, and reward practices in Islamic financial institutions. Aims: This study examines employee performance assessment by focusing on human resource quality and organizational culture within the institutional context. Results: Quantitative analysis using census data from 50 employees shows that human resource quality is prominently reflected in performance assessment results, while organizational culture does not demonstrate standalone statistical relevance, although both variables jointly account for a substantial proportion of performance variation. Novelty: The study emphasizes specific internal conditions that are often overlooked in prior research. Implications: The findings provide empirical insight for managerial evaluation of competency alignment and internal work systems to support sustainable employee performance assessment. Highlights Human resource quality is clearly reflected in employee performance assessment outcomes. Educational mismatch and uneven technical skills remain key internal organizational conditions. Organizational culture contributes jointly with human resource quality within performance assessment. Keywords Human Resource Quality, Organizational Culture, Employee Performance, Islamic Banking, Performance Assessment